The Probability of the Fifth Dimension and the Relevant Theories (A Scientific-Philosophical Analysis) - sadrodin nadei; hoseyn kalbasi ashtari; amir hoseyn banki purfard (حکمت و فلسفه, 2009)
While analyzing different theories on dimensions in mathematics and physics, this article argues for the existence of another dimension, different from other dimensions through philosophical reasons and gives a breakthrough to overcome the mental constraints for understanding greater dimensions and specially, by various reasons and proofs, introduces the expansion or macromic dimension as the fifth dimension. This dimension is associated with an object's largeness or smallness and depends on "scale". In fact the difference between objects from macroscopic and microscopic viewpoints that is familiar for human being since ancient times deals with this material dimension. The consequent results of assuming more than 3 dimensions may influence the domain of philosophical issues and other relevant domains. More than 40 of these domains have been listed at the end of this article.